Physical Rehabilitation in Patients with Chronic Heart Failure and Chronic Obstructive Pulmonary Disease - Roman Evgenyevich Tokmachev, Andrey Valerievich Budnevsky, Andrey Yakovlevich Kravchenko, Olysheva Irina Alexandrovna, Volynkina Anna Petrovna, Tatiana Alexandrovna Chernik, Us Margarita Andreevna, (Pakistan Journal of Medical & Health Sciences, 2022)
Despite all the efforts of medical services, the socio-economic damage caused by chronic heart failure (CHF) is increasing. Approximately 10-40% of patients with CHF also suffer from chronic obstructive pulmonary disease (COPD). The comorbid course of these pathologies aggravates the prognosis of patients. Moderate physical activity is recommended as a non-drug therapy for both pathologies. The aim of the study: was to evaluate the effectiveness of physical rehabilitation in patients with chronic heart failure and chronic obstructive pulmonary disease by determining the levels of NT-proBNP, high-sensitivity C-reactive protein, IL-1β, IL-6, TNF-α. Methods: The study included 240 patients with CHF. After the initial examination, the patients were divided into groups depending on the presence or absence of COPD and the value of LVEF. Subsequently, each group was divided into a subgroup that took part in physical rehabilitation in addition to standard medical therapy and another one consist of patients that received only standard therapy. A year later, the levels of NT-proBNP, high-sensitivity C-reactive protein, IL-1β, IL-6 and TNF-α were re-determined. Results and Conclusion: CHFpEF patients have higher levels of hs-CRP and pro-inflammatory cytokines compared to patients with CHFrEF. The combination of COPD and CHF enhances systemic inflammation and myocardial remodeling processes, determined by the level of NT-proBNP in comparison with the isolated course of CHF. Physical rehabilitation in patients with a comorbid course of COPD and CHF is accompanied by a significant decrease in the levels of pro-inflammatory cytokines, hs-CRP and NT-proBNP.